EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF PADA PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 3 DI MI MIFTAHUS SA’ADAH KARANGSONO - Khofifah, Ulin; Zuhri, M. Robith Hidayatullah; Khofifah, Ulin Ni’matul; Rianto, Tomy; Al Azhari, M.Luthfi Afif (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This study aims to analyze the effectiveness of using learning media in enhancing critical thinking skills and competencies among third-grade students at MI Miftahus Sa’adah. Given the importance of critical thinking skills in the 21st century, learning media is considered a tool that can facilitate an interactive and in-depth learning process. This research employs a quantitative approach with a quasi-experimental design to measure the differences in critical thinking skills and student competencies before and after the implementation of learning media. The results indicate that the use of learning media significantly improves students' critical thinking abilities, particularly in problem-solving, analysis, and creativity.